Achievements and perspectives in the breeding of tropical grasses and legumes - Miles, John W. (Brazilian Society of Animal Husbandry, 2001)
Pasture and forage plant breeding is complicated by the perennial nature of the plants, the diversity of environments in which improved cultivars will be used, and the complex criteria of merit involved, criteria that necessarily include some measure of impact on the efficiency of animal production. While pasture plant breeding in the temperate zone is a demonstrably productive activity, the record of success for the tropical species --"success" measured by release and adoption of bred cultivars --is less convincing, in spite of four decades of activity in numerous public sector breeding programs and a large published literature. The difference is at least partly owing to the less developed state of pasture research in general in the tropics. More specifically, the reasons for the lack of success of tropical pasture plant breeding can be classified as: i) inadequate understanding of the socioeconomic environment in which the bred cultivars are to be used, ii) inadequate level and stability of institutional support, and iii) inherent biological obstacles. It appears that in most cases the biological obstacles, while sometimes formidable, are the least constraining to success. Until responsibility for tropical pasture plant breeding is assumed by the private sector (as it largely has been in the temperate zone) the single factor that would most improve chances of success (or at least avoid many of the failures) is intimate contact and constant communication between the public sector plant breeder and the seed industry that is the vehicle for diffusion of his new bred cultivars.